2017
DOI: 10.1016/j.jtcvs.2017.04.085
|View full text |Cite
|
Sign up to set email alerts
|

Improving coronary artery bypass grafting readmission outcomes from 2000 to 2012 in the Medicare population

Abstract: In a large cohort of Medicare patients undergoing coronary artery bypass grafting over 13 years, there was a significant decrease in 30-day readmission rates, a reduction in readmission for wound infections, and reduced mortality during the readmission episode, despite an increase in patient comorbidities. The improvement in readmission rates was seen regardless of patient variables examined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…In studies where history of comorbidities was reported, diabetes (range: 12 to 69%) and hypertension (range: 37 to 95%) were relatively common in patients undergoing CABG. While most studies included patients, who had either isolated or combined CABG procedures, 22 studies [ 8 , 13 , 26 , 29 , 31 , 33 , 35 37 , 39 , 40 , 45 – 48 , 50 , 51 , 54 , 56 , 58 , 59 , 62 ] included only those who underwent isolated CABG procedures. The included studies varied widely (range: 15 to 100%) in the proportion of elective procedures (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In studies where history of comorbidities was reported, diabetes (range: 12 to 69%) and hypertension (range: 37 to 95%) were relatively common in patients undergoing CABG. While most studies included patients, who had either isolated or combined CABG procedures, 22 studies [ 8 , 13 , 26 , 29 , 31 , 33 , 35 37 , 39 , 40 , 45 – 48 , 50 , 51 , 54 , 56 , 58 , 59 , 62 ] included only those who underwent isolated CABG procedures. The included studies varied widely (range: 15 to 100%) in the proportion of elective procedures (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-three studies [ 8 , 13 , 28 , 31 , 35 , 36 , 39 41 , 43 , 46 , 48 , 50 , 52 , 54 , 55 , 57 , 58 , 60 , 62 64 , 66 ] reported the causes of 30-day readmission after CABG (Fig. 4 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations